Role of nuclear poly(A) binding protein 1 in tumors - SHI Lizhou, HAN Wei, SHEN Xiaojun (Jichu yixue yu linchuang)
Nuclear polyadenosine-binding protein 1(PABPN1)is the only known polyadenosine-binding protein in the cell nucleus of mammals. The first attention was resulted from relevant research on oculopharyngeal muscular dystrophy (OPMD), where mutations and aggregation of PABPN1 were found to be the main pathogenesis of the disease. Recently, PABPN1 is found to be abnormally expressed in some tumor tissues, and confirmed to be involved in regulating selective polyadenylation, which leads to the occurrence and development of various human tumors. This article briefly introduces the structure and function of PABPN1, reviews progress of research related to PABPN1 and tumors in recent years, and provide our thought for exploring point potential pathways for future research on the role and mechanism of PABPN1 in the occurrence and development of tumors.